Incidence and severity of cucurbit powdery mildew in Uttar Pradesh - ABRAR M. KHAN2, AZMAT ULLAH KHAN1 and (Indian Phytopathology, 2012)
Survey of cucurbit powdery mildew in upper Gangetic plains and hilly areas in the state of Uttar Pradesh in northern India indicated that the disease was prevalent throughout the region. Of the 14 cultivated and three wild cucurbits encountered during the survey, 11 cultivated and all the three wild ones were found to be infected. Three of them, viz., Citrullus lanatus ver.fistulosus (Stocks), Dathie and Fuller, Momordica charaniia L. and Trichosanthes cucumerina L. showed some degree of resistance. The disease was more severe during March to May and September to November, mild to moderate during December to February and altogether absent during June to August. Peritheeia of Eryslphe cichoracearum DC. were observed during December to February only on Coccinia cordifolia (L). Cogn. and Benincasa hispida (Thum.) Cogn.